Neural differentiation of human pluripotent stem cells for nontherapeutic applications: Toxicology, pharmacology, and in vitro disease modelling [Review article]. - Yap, May Shin *; Nathan, Kavitha R. *; Yeo, Yin *; Lim, Lee Wei; Poh, Chit Laa *; Richards, Mark; Lim, Wei Ling *; Othman, Lekhsan; Heng, Alexis Boon Chin * (Hindawi Publishing Corporation, 2015)
Human pluripotent stem cells (hPSCs) derived from either blastocyst stage embryos (hESCs) or reprogrammed somatic cells (iPSCs) can provide an abundant source of human neuronal lineages that were previously sourced from human cadavers, abortuses, and discarded surgical waste. In addition to the well-known potential therapeutic application of these cells in regenerative medicine, these are also various promising non-therapeutic applications in toxicological and pharmacological screening of neuroactive compounds, as well as for in vitro modeling of neurodegenerative and neurodevelopmental disorders. Compared to alternative research models based on laboratory animals and immortalized cancer-derived human neural cell lines, neuronal cells differentiated from hPSCs possess the advantages of species specificity together with genetic and physiological normality, which could more closely recapitulate in vivo conditions within the human central nervous system. This review critically examines the various potential non therapeutic applications of hPSC-derived neuronal lineages and gives a brief overview of differentiation protocols utilized to generate these cells from hESCs and iPSCs.